The Effect of Perceived Overqualification on Creative Performance: Person-Organization Fit Perspective - Zhang, Man; Wang, Fan; Li, Na (Frontiers in Psychology, 2021)
In today’s business world, the phenomenon of overqualification is widespread. The organization needs to consider how to motivate the overqualified employees to utilize their qualifications by, for example, promoting creative performance. Based on P-O fit theory, this study explored when and how employees who feel overqualified can engage in creative performance. Data were collected from 170 supervisor-subordinate dyads of 41 groups across two timepoints data in ten manufacturing companies in China. Results revealed: (1) perceived overqualification is positively related to organizational identification when employee development-oriented organizational culture is strong but negatively related to organizational identification when employee development-oriented organizational culture is weak, (2) organizational identification is positively related to creative performance, (3) the indirect relationship between perceived overqualification and creative performance via organizational identification is moderated by employee development-oriented organizational culture. We provide several theoretical contributions to the overqualification literature and make some suggestions for how to motivate the overqualified employees to use their surplus qualifications within the organizations.